Alkaline Phosphatase as Serum Tumor Marker in Osteosarcoma - Zuhair Bhatti, Khadija Kiran, Muhammad Shoaib, Seerat Un Nisa, Ahmar Arif (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To reassess the high specificity of alkaline phosphatase as a serum tumor marker in patients with osteosarcoma Study type: Retrospective cohort study Study place and duration: Department of Orthopedics, DHQ Hospital Gujranwala from January 2013 to June 2021 Methods: The medical record of 140 osteosarcoma patients were reviewed retrospectively, who received treatment for osteosarcoma during January 2015 and June 2021. According to clinical factors at diagnosis, the difference in prevalence of increased ALP was assessed using Fisher`s extract test and χ2 test. In the groups with normal and high level of serum ALP at presentation, the disease-free survival (DFS) and overall survival (OS) were compared using The Kaplan–Meier estimate. At presentation the prognostic ability of increased ALP was examined using Cox regression analyses. For determination of therapeutic steps and survival related changes in levels of ALP during therapy and survival related response of ALP to therapy, Linear Mixed model (fixed model) was used. Results: Sensitivity, specificity , Positive predictive value, negative predictive value, PLR, NLR and DOR of ALP in Metastatic osteosarcoma at 15 months follow up was 55.4%, 80.3%, 62.1%, 74.2%, 3.14, 0.864 and 5.241 respectively. Similarly, Sensitivity, specificity , Positive predictive value, negative predictive value, PLR, NLR and DOR of ALP in Metastatic osteosarcoma at 3 years follow up was 56.4%, 92.5%, 83.1%, 70.1%, 6.321, 0.632 and 8.543 respectively. Conclusion: ALP has been found to be a very important tumor marker having high specificity in patients with osteosarcoma.